Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) pada Pokok Bahasan Stoikiometri di Kelas X SMA/MA - Anugrah, Putri Suci; Rery, Radjawaly Usman; Erviyenni, Erviyenni (Jurnal Riset Pendidikan Kimia (JRPK), 2022)
The development of this LKPD aims to develop LKPD based on the type of cooperative learning model Think-Pair-Share (TPS) which is valid based on validator assessments and practical based on user response tests, namely teachers and students. A valid assessment is based on 5 aspects of feasibility, namely the feasibility of the content, the feasibility of the characteristics of the TPS learning model, the feasibility of language, the feasibility of presentation and the feasibility of graphics. This research uses the type of development research (R&D) with 4D stages and is only carried out until the development stage of limited trials. The assessment instruments used were the validation sheet and the user practicality test questionnaire. Assessment of the user practicality test questionnaire was given to 2 teachers and 20 students from SMAN 1 Pekanbaru and SMAN 6 Pekanbaru. The results of the LKPD validation were declared valid with scores on the aspects of content feasibility, TPS model characteristics, language, presentation and graphic of 95.83%, 95%, 89.58%, 91.67% and 95.83%, respectively. While the results of the user practicality test were declared practical by obtaining an average score percentage of 92% by teachers with very good criteria and 88.03% by students with very good criteria. Keywords :Student Activites Worksheet, TPS Learning Model, Stoichiometry